MENGELOLA GOLF DENGAN WEB (Information Technology and Telematics, 2014)
Abstract - Gombel, Semarang Golf (GGS) is one of the golfing arena in Semarang. To lease the golf course itself are still using manual way, so that the required application information online system a while want to Transact rental golf course. To solve the solution then the researchers create an online application at the golf course rentals Gombel, Semarang (GGS) Golf. This information system aims to help customers simplify the process of leasing and marketing computerized golf courses as well as help the maintainer Gombel, Semarang Golf (GGS) to promote golf rental services and amenities. This information system development method using prototype and his programming language for using PHP with a MySQL database as well as for perancangannya using UML (Unifed Modeling Language) With the information system web-based golf course management is expected to address the problems of rental golf course in Gombel, Semarang Golf. Keywords: Information System, Rental a golf course, GGS, PHP, MySQL